Robust design to optimize client–server bi-directional communication for structural analysis web applications or services. (October 2017) - Calvo, J.; Gracia, J.; Bayo, E.
Highlights: Client–server communication factors for structural SaaS are identified DoE techniques are used to identify relevant factors and its interactions Data size and serialization language factors have a significant influence JSON and AJAX combination is the most efficient but WebSocket has wider possibilities Abstract: Current trends in web application development favours bi-directional communication between front-end and back-end applications instead of the traditional ones where the front-end is constantly monitoring the back-end. This way of communication improves the user experience and this work tries to find the best bi-directional way of communication particularized to structural analysis software as a service or web applications. The effects of the most significant factors have been studied to optimize the total time involved in the communication, which is comprised of: time spent sending data from the client to the server, server data processing, and time consumed returning the data back. Design of experiments (DoE) techniques have been used to characterize the influence of four factors: serialization language, communication protocol, amount of data (size of the structure measured by the number of elements), and server post-processing. Moreover, factors like server workload and network congestion have also been addressed. The first factor is dealt with as a nuisance factor whose influence is to be minimized, and the second one as an uncontrollable variable.